2019
DOI: 10.1108/jeee-08-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

A structural model assessing key factors affecting women’s entrepreneurial success

Abstract: Purpose The present study aims to investigate the influence of key factors on the success of women micro-entrepreneurs in select states of India. Design/methodology/approach An empirical study is carried out to understand the influence of the psychological, socio-cultural, skill and resource-related factors on the success of women entrepreneurs. To achieve the set goal, a comprehensive questionnaire is developed for collecting data and is analyzed using the t-test, the chi-square test and structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 61 publications
(34 reference statements)
6
45
0
2
Order By: Relevance
“…The findings also support the UET, which suggest the importance of viewpoint of the management in forecasting the outcome of the firm (Child, 1972;Hambrick, 2007). The strengths of embracing pro-activeness in business, risk-taking ability and innovativeness (Chatterjee et al, 2019) support tech startup entrepreneurs to accept bricolage, which prepares them to identify workable solutions for the emerging challenges. The results also show that higher levels of bricolage behavior among tech startup entrepreneurs led to a better level of overall resource advantage that conforms to the study (Steffens et al, 2013).…”
Section: Discussionsupporting
confidence: 57%
“…The findings also support the UET, which suggest the importance of viewpoint of the management in forecasting the outcome of the firm (Child, 1972;Hambrick, 2007). The strengths of embracing pro-activeness in business, risk-taking ability and innovativeness (Chatterjee et al, 2019) support tech startup entrepreneurs to accept bricolage, which prepares them to identify workable solutions for the emerging challenges. The results also show that higher levels of bricolage behavior among tech startup entrepreneurs led to a better level of overall resource advantage that conforms to the study (Steffens et al, 2013).…”
Section: Discussionsupporting
confidence: 57%
“…However, the all-inclusive outcome of the investigation has not yet been proven. The likely reason may be a lack of critically evaluating numerous factors accountable for the success (Chatterjee et al , 2019). Hence, this study concentrated on subjective career success, operationalised as having three independent dimensions: career satisfaction, perceived career achievement and perceived financial attainment (Lau et al , 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal locus of control is related to entrepreneurship because owners must believe that their own actions determine the rewards (business outcomes) they obtain. Many literature studies have revealed through empirical findings that internal locus of control is an entrepreneurial characteristic that has the major drive toward entrepreneurial activity (Chatterjee, Das and Srivastava, 2019).…”
Section: Entrepreneurial Traits and Characteristics (Dependent Variabmentioning
confidence: 99%
“…Some researchers claimed that innovation is a primary intention in putting up a business venture. Entrepreneurs were reported to be more innovative than the non-entrepreneurs (Chatterjee, et al, 2019;Gurol and Atsan, 2006;Thomas and Mueller, 2000;Koh, 1996).…”
Section: Entrepreneurial Traits and Characteristics (Dependent Variabmentioning
confidence: 99%